Theory for nonlinear section model tests in the wind tunnel for cable-supported bridges. (1st September 2022) - Maheux, Sébastien; King, J. Peter C.; El Damatty, Ashraf; Brancaleoni, Fabio
Abstract: Wind tunnel tests for cable-supported bridges have been utilized extensively to achieve stable and wind resistant bridge designs over the past decades. Section model tests are by far the most common tests carried out. This is mainly due to their simplicity and their cost effectiveness. However, in order to reach this level of simplicity, some generalizations are required. One of them is the assumption that the bridge structure behaves linearly. For most bridges, this seems reasonable, but for very long spans, the cable system plays a dominant role in providing the vertical and torsional stiffnesses. Hence, as the cable system behaves nonlinearly, very long spans show a stronger nonlinear behavior, especially for suspension bridges. Furthermore, the theoretical demonstrations that have been made with regard to structural dynamic instabilities associated with geometric nonlinearities in suspension bridges confirm the need for a better understanding of the possible interaction between nonlinear structural effects and aeroelastic effects. Therefore, this paper presents the theoretical developments for a new type of section model test for bridges that accounts for geometric nonlinearities of the bridge structure. This theory for nonlinear section model tests starts from two-mode nonlinear generalized stiffness parameters obtained using nonlinear pushover analysis, which need to be scaled using a specifically developed procedure. Using eleven numerical models of cable-supported bridges, the assumptions made in the theory for nonlinear tests are then validated. The proposed scaling procedure is also tested. Highlights: Theory for nonlinear wind tunnel tests for cable-supported bridges is developed. Section model tests accounting for nonlinear structural vertical–torsional coupling. Scaled nonlinear structural behavior representative of a cable-supported bridge.